Varietal effects on Greenhouse Gas emissions from rice production systems under different water management in the Vietnamese Mekong Delta - Vo, Thi Bach Thuong; Johnson, Kristian; Wassmann, Reiner; Sander, Bjoern Ole; Asch, Folkard (Wiley, 2024)
Rice production accounts for 15% of the national Greenhouse Gas (GHG) emissions and Vietnam aims at reducing emissions from rice production by focusing on changing farming practices. However, the potential for mitigation through the selection of different rice varieties is still poorly understood. A two‐year field screening of 20 rice varieties under continuous flooding (CF) and alternate wetting and drying (AWD) irrigation was conducted in the Vietnamese Mekong Delta (VMD), Vietnam, employing the closed chamber method for assessing GHG emissions. The results confirmed that varietal variation was the largest for methane (CH4) emissions under CF. Across the varietal spectrum, CH4 emissions were more important than nitrous oxide (N2O) (accounts for less than 2% of the CO2e) with the lowest emitting variety showing 243 kg CH4 ha−1 and the highest emitting variety showing 398 kg CH4 ha−1 emissions as compared to 0.07 kg N2O ha−1 and 0.76 kg N2O ha−1 emissions, respectively. Under AWD, CH4 emissions were generally strongly reduced with the varietal effect being of minor importance. Compared with IPCC default values, the data set from the two seasons yielded higher Emission Factors (EFs) under CF (2.92 and 3.00 kg ha−1 day−1) as well as lower Scaling Factors (SFs) of AWD (0.41 and 0.38). In the context of future mitigation programs in the VMD, the dry season allows good control of the water table, so varietal selection could maximize the mitigation effect of AWD that is either newly introduced or practised in some locations already. In the wet seasons, AWD may be difficult to implement whereas other mitigation options could be implemented such as selecting low‐emitting cultivars.